The Effect of Financial Planning on Consumer Debt Management: The Role of Financial Literacy, Self-Efficacy, and Financial Motivation - Jumady, Edy; Alam, Syamsul; Hasbiyadi, Hasbiyadi; Fajriah, Yana; Anggraini, Yaisa (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This qualitative study investigates the complex interplay between financial literacy, financial behavior, self-control, debt management, and financial well-being. Utilizing in-depth interviews with a purposively selected group of individuals engaged in financial planning to manage personal or household debt, the research aims to explore how financial literacy, self-efficacy, and financial motivation mediate the relationship between financial planning and consumer debt management. The methodology encompasses a thematic analysis of participants' narratives to identify and interpret the underlying themes related to financial management practices. Findings reveal a multifaceted relationship where financial literacy emerges as a foundational element, enhancing participants' ability to manage debt effectively. High financial self-efficacy, influenced by literacy, motivates proactive financial behaviors, leading to improved financial well-being. Conversely, low self-control and procrastination were identified as significant barriers to effective debt management. The study also highlights the pivotal role of quantitative literacy and material values in shaping financial behavior, with strong quantitative skills and lower materialism associated with forward-looking financial decisions. These insights underscore the need for comprehensive financial education that addresses not only the cognitive aspects of financial decision-making but also the psychological factors influencing financial behaviors. Tailoring financial education to individual needs and contexts is critical for enhancing financial literacy, self-efficacy, and motivation, ultimately leading to better debt management and financial health.